Flexible photonic devices based on dielectric antennas. (21st January 2020) - Benali, Abdennacer; Claude, Jean-Benoît; Granchi, Nicoletta; Checcucci, Simona; Bouabdellaoui, Mohammed; Zazoui, Mimoun; Bollani, Monica; Salvalaglio, Marco; Wenger, Jérôme; Favre, Luc; Grosso, David; Ronda, Antoine; et al.
Abstract: Flexible and stretchable photonics are emerging fields aiming to develop novel applications where the devices need to conform to uneven surfaces or whenever lightness and reduced thickness are major requirements. However, owing to the relatively small refractive index of transparent soft matter including most polymers, these materials are not well adapted for light management at visible and near-infrared frequencies. Here we demonstrate simple, low cost and efficient protocols for fabricating Si1− x Ge x -based, sub-micrometric dielectric antennas over record scales (50 mm wafers) with ensuing hybrid integration into different plastic supports. The transfer process has a near-unity yield: up to 99.94% for disordered structures and 99.5% for the ordered counterpart. Finally, we benchmark the optical quality of the dielectric antennas with light scattering measurements, demonstrating the control of the islands structural color and the onset of sharp Mie modes after encapsulation in plastic. Thanks to the ease of implementation of our fabrication methods, these results are relevant for the integration of SiGe-based dielectric Mie resonators in flexible substrates over large surfaces.